TECHNOLOGICAL FEATURES OF THE CREATION AND USE OF THE SECTORAL ELECTRIC COMMERCE - Perov, V. O.; Vakulenko, A. S.; Yakunin, O. K. (Science and Transport Progress, 2008)
This article is devoted to a question of introduction and use of electronic system of carrying out of competitions. The stages of conducting a competition are considered, the drawbacks of conducting competitions by hand are defined and the main features of creating a system for automation of process of carrying out competitions are outlined in this article.